HUBUNGAN JENIS SUMBER AIR DAN PERSONAL HYGIENE DENGAN PENYAKIT DERMATITIS DI DESA BANTAN TIMUR KECAMATAN BANTAN KABUPATEN BENGKALIS - Eliza Fitria; Linda Hayani (Ensiklopedia of Journal, 2021)
Skin diseases is one of the most common diseases in tropical countries, including Indonesia. Dermatitis is an inflammation of the skin characterized by itching, which can be in the form of thickening or reddish spots, clustered or scattered, sometimes scaly, watery and others due to the skin surface is exposed to materials or elements in the environment (exogenous factors). In 2015, Dermatitis was included in the 8 largest diseases in the working area of Selatbaru health center that continues to increase every year until early 2020. The purpose of this study to determine the correlation water source types and personal hygiene with Dermatitis incidence in Darul Takzim Bantan Timur Village Bantan District Bengkalis Regency. The design of this research quantitative research with Cross Sectional approach, the number of samples are 56 respondents were taken by purposive sampling technique. The analysis used in this research is univariate and bivariate analysis. The results showed that there was a correlation between water source types and Dermatitis incidence p value = 0,000, which means p value < α and there was no correlation between personal hygiene and Dermatitis incidence p value = 0,555, which means p value > α in Darul Takzim Bantan Timur Village Bantan District Bengkalis Regency. For that it is suggestions for Bantan Timur government to make a clean water source procurement program, issuing policy about the prohibition waste disposal to the trench and collaborate with Selatbaru health center to conduct quality of physically, bacteriologically, and chemically on each water source, find solutions to solve the water source problems, and socializate to public about clean and healthy lifestyle especially the health requirements of water source.